A green approach for Ochratoxin A determination in coffee infusions - Cina, Mariel (2022)
Ochratoxin A (OTA) is a secondary metabolite of filamentous fungi and is considered within the 2B group by IARC. OTA can be found in a variety of food commodities and beverages. In this study, a new methodology for the detection and quantification of OTA in coffee beverages was developed and validated. The extraction procedure was based on dispersive liquid-liquid microextraction with solidification of a floating organic drop (DLLME-SFO). The extract was analyzed by UHPLC-(ESI+)-MS/MS. The methodology was sensitive, with a LOD and LOQ of 0.3 and 0.9 ng/mL, respectively, and linearity was demonstrated between 0.3 and 70 ng/mL, with a correlation coefficient (R2) of 0,9962. The relative standard deviations varied from 1.1 to 8.7% (n=3). In addition, satisfactory extraction relative recovery was obtained (88.3%, with an enrichment factor of 7-folds). This methodology was evaluated through two green analytical metrics: the Green Certificate and the AGREE software. Thus, an A-category and 0.54 points were obtained, respectively. Finally, the methodology was applied to commercial sugar added-roast coffee (coffee bag) samples.